Application of Autoregressive Integrated Moving Average (ARIMA) for Forecasting Inflation Rate in Indonesia - Jova Edri Saputra; Werry Febrianti (Jurnal Matematika, Statistika dan Komputasi, 2025)
Inflation is one of the indicators to maintain economic stability. Controlling inflation reflects the success of economic growth, while very high or volatile inflation can lead to economic instability. The purpose of this research is to forecast the time series data of inflation rate in Indonesia until the end of 2024 using ARIMA method. The data used in this study are secondary data of monthly inflation rates in Indonesia from January 2003 to May 2024 obtained from the Bank Indonesia website. Based on the research results, the optimal model for forecasting the inflation rate in Indonesia until the end of 2024 is ARIMA (1,0,1) with a MAPE of 6.91%. The forecasting results show a stable and not too significant increase and are still within the target range set by Bank Indonesia and the Government, which is between 1,5% and 3,5% for 2024.